Central hypothyroidism related to antipsychotic and antidepressant medications: an observational study and literature review. Issue 2 (8th March 2022) - Keen, Frederick; Chalishazar, Anuja; Mitchem, Kelly; Dodd, Alan; Kalhan, Atul
Abstract : Objective: To investigate the final diagnosis and clinical outcome of patients referred to endocrinology in our district general hospital with biochemical isolated central hypothyroidism (CeH), and whether there is an association between this biochemical picture and treatment with antidepressant and antipsychotic medications. Methods: We performed a retrospective observational study of patients referred to endocrinology with unexplained biochemical isolated CeH over a 5-year period. Results: Of the 29 patients included in the study, 4 were found to have a partially empty or empty sella and 1 to have a bulky pituitary gland which was deemed to be an incidental radiological finding. No patients had any clinically significant pathology. On reviewing their medications, 18/29 (62%) were found to be on psychotropic medications. Conclusions: Our study suggests a relationship between patients on psychotropic medications and biochemical isolated CeH, an association only described in a very limited amount of literature prior to this. The mechanism behind this may be suppression of TSH secretion via antagonism of the dopamine-serotoninergic pathway. Determining a correlation between psychotropic medications and isolated CeH could lead to the avoidance of further radiological investigations and unnecessary anxiety for patients. However, a larger observational study is needed to provide further evidence to support/refute our finding.